Partially bio-based processable polyimides based on aromatic diamine derived from cardanol - Shingte, Rahul D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (green Materials, 2017)
A partially bio-based aromatic diamine, namely, 1,1-bis(4-aminophenyl)-3-pentadecylcyclohexane (BAC15) was synthesized starting from cardanol. A series of polyimides were synthesized by one-step high-temperature solution polycondensation of BAC15 with aromatic dianhydrides. Copolyimides were also synthesised by polycondensation of various compositions of BAC15 and 4,4’-oxydianiline with 3,3’,4,4’-biphenyl tetracarboxylic dianhydride. Inherent viscosities and number average molecular weights of (co)polyimides were in the range 0.33-1.4 dL/g and 14700-31900 g/mol, respectively, indicating formation of reasonably high molecular weight polymers. Polyimides were soluble in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran and could be cast into transparent, flexible and tough films from their solutions in chloroform. (Co)polyimides exhibited Tg in the range 161–254 °C. The lowering of Tg could be attributed to the presence of flexible pentadecyl chains which act as “packing disruptive” groups. The temperature at 10% weight loss (T10) of (co)polyimides was in the range 490–515 °C demonstrating their good thermal stability. The virtue of solubility and large gap between Tg and T10 offers (co)polyimides opportunities of both solution as well as melt processability. Copolyimides containing pendent pentadecyl chains exhibited pretilt angle in the range 2.51-2.75° indicating their potential application as alignment layer in liquid crystal display devices.

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.